Explore Fun & Facts Board Games - Taman Ular Negeri Perlis - Yusdi Ismail; Mohd Zulkifli Manaf; Norzakiah Mohamed Bakhari (Malaysia Journal of Invention and Innovation, 2023)
A gaming board called Xplore Fun Facts draws its inspiration from snake and ladder games. This game board's concept was developed based on Perlis Snake Park, one of the city's most well-known tourist attractions. Visitors to Snake Park can enjoy playing this creative toy. Students and the general public can also participate in the game to learn more about the different kinds of reptiles that can be found in the snake park. An interactive component like QR codes is one of the game's features. The participants can choose between three sets of questions by scanning the QR code. The ease of use and entertaining facts about the snake park's reptiles are two benefits of this innovative product. This product can be used to raise the degree of awareness of visitors to Taman Ular regarding the habitat that dwell in the garden, according to the questionnaire that was issued to the users.